2013
DOI: 10.1016/j.biopsych.2012.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Schizophrenia Risk Variants Jointly Modulate Total Brain and White Matter Volume

Abstract: Background Thousands of common single nucleotide polymorphisms (SNPs) are weakly associated with schizophrenia. It is likely that subsets of disease-associated SNPs are associated with distinct heritable disease-associated phenotypes. Therefore, we examined the shared genetic susceptibility modulating schizophrenia and brain volume. Methods Odds ratios for genome-wide SNP data were calculated in the sample collected by the Psychiatric GWAS Consortium (8,690 schizophrenia patients and 11,831 controls, excludi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
103
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(113 citation statements)
references
References 32 publications
5
103
5
Order By: Relevance
“…[ [15][16][17][18]. This patient sample consisted of ARMS and FEP patients, but without schizophrenia and bipolar disorder patients or healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ [15][16][17][18]. This patient sample consisted of ARMS and FEP patients, but without schizophrenia and bipolar disorder patients or healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…PSRS calculation PSRS were calculated, following the suggestions of Wray et al [34], by taking LD pruned loci associated with white matter volume identified by Terwischa van Scheltinga et al, 2013 [15]. All 186 SNPs could be used to calculate the PSRS.…”
Section: Mri Acquisitionmentioning
confidence: 99%
“…41,118,119 Moreover, because a polygenic contribution to MDD with psychotic features can be expected, future genomewide association studies on representative samples MDD with psychotic features may afford quantitative risk scores to be subsequently used in studies investigating the relationship between robust imaging phenotypes and polygenic risk scores. 120,121 Finally, there should also be neuroimaging studies applying a dimensional approach to the evaluation of psychosis associated with MDD, with both subthreshold and full-blown psychotic experiences rated along a continuum of severity, on a background of major depressive symptoms. There is a significant prevalence of subthreshold psychotic-like experiences in the general population 122 and in subjects with less severe major depressive episodes, 123 and there is a growing recognition that psychotic symptoms may best be viewed as falling along a continuum of severity in MDD rather than solely as a subcategory of severe MDD.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…Examination of the cumulative effects of inheriting multiple risk alleles—each of which are significantly or nominally associated with disease risk—has been able to powerfully differentiate groups of cases from controls in independent population‐based studies [Purcell et al, 2014, 2009; Patel et al, 2010; Ayalew et al, 2012; Terwisscha van Scheltinga et al, 2012]. However, despite phenotypic aggregation within families [McGuffin et al, 2003; Lichtenstein et al, 2009], no studies have so far examined polygenic risk incorporating these common genetic factors in a family context in adults, with only one group to date reporting on polygenic risk in adolescent offspring of individuals with BP [Whalley et al, 2012, 2013].…”
Section: Introductionmentioning
confidence: 99%